The impact of periodontal treatment on healthcare costs in newly diagnosed diabetes patients: evidence from a German claims database - Blaschke, Katja; Hellmich, Martin; Samel, Christina; Listl, Stefan; Schubert, Ingrid (Diabetes research and clinical practice, 2021)
Aims - There is sufficient scientific evidence for the bidirectional association between periodontal diseases and diabetes. In this context, we hypothesized that periodontal treatment leads to lower healthcare costs in newly diagnosed diabetes patients by promoting a milder disease course. - Methods - A total of 23,771 persons were investigated who were continuously insured by German health insurances between 2011 and 2016, 18 years or older, and newly diagnosed with diabetes in 2013. The study population was divided into a periodontal treatment and control group (no periodontal treatment). The average treatment effect of a periodontal treatment on various types of healthcare costs (inpatient, outpatient, drug costs) was analyzed by a doubly robust method. - Results - Finally, 5.3% of the study population could be assigned to the treatment group. In newly diagnosed diabetes patients with periodontal treatment, a reduction in total healthcare costs (0.96, 95%CI 0.89; 1.04), inpatient costs (0.87, 95%CI 0.69; 1.08), diabetes-related drug costs (0.93, 95%CI 0.84; 1.03) and other drug costs (0.97, 95%CI 0.89; 1.05) could be shown compared to the control group. - Conclusions - This study provides evidence that periodontal treatment for diabetes patients reduces healthcare costs. Fewer diabetes-specific complications and hospitalizations are expected.
Available online 24 December 2020
Gesehen am 05.05.2021